Detection, quantification and genetic characterization of six major non-O157 Shiga toxin-producing Escherichia coli serogroups and E. coli O104 in feedlot cattle feces - Belagola Shridhar, Pragathi (Kansas State University, 2017)
Cattle feces are a major source of six Shiga toxin-producing E. coli (STEC) serogroups, O26, O45, O103, O111, O121, and O145, called non-O157 STEC, responsible for >70% of non-O157 STEC-associated human illnesses. Another E. coli serotype, O104:H4, a hybrid pathotype of enteroaggregative and STEC, was responsible for a large outbreak of foodborne illness in Germany. Studies were conducted to develop and validate culture- and PCR-based methods to detect and or quantify six non-O157 E. coli serogroups and E. coli O104 in cattle feces, and genetically assess their virulence potential, based on DNA microarray and whole genome sequencing (WGS). Two multiplex quantitative PCR (mqPCR) assays (assay 1: O26, O103 and O111; assay 2: O45, O121 and O145), targeting serogroup-specific genes, were developed and validated for the detection and quantification of six non-O157 E. coli in cattle feces and was compared to culture-based and end-point PCR methods. The mqPCR assays detected higher proportion of fecal samples as positive for one or more non-O157 E. coli serogroups compared to culture-based and end-point PCR methods. Spiral plating method was validated to quantify six non-O157 E. coli serogroups in cattle feces, and was compared to mqPCR assays. The mqPCR assays quantified higher proportion of fecal samples positive for one or more non-O157 E. coli serogroups compared to spiral plating method, however, unlike mqPCR, spiral plating method quantifies serogroups positive for virulence genes. Quantification by either mqPCR or spiral plating identified a subset of cattle that was shedding non-O157 E. coli at high concentrations (≥ 4 log CFU/g of feces), similar to E. coli O157. Identification of Shiga toxin subtypes associated with non-O157 E. coli serogroups isolated from cattle feces revealed a variety of subtypes, with stx1a and stx2a being the most predominant. Microarray-based analysis of six non-O157 E. coli serogroups isolated from cattle feces revealed the presence of stx, LEE-encoded, and other virulence genes associated with human illnesses. Analysis of WGS of STEC O145 strains isolated from cattle feces, hide and human clinical cases revealed similarity in virulence gene profiles, suggesting the potential of cattle E. coli O145 strains to cause human illnesses. Shiga toxin 1a was the most common stx subtype, followed by stx2a, and stx2c. The strains also carried LEE-encoded, and plasmid-encoded virulence genes. Model adjusted prevalence estimates of E. coli O104 in cattle fecal samples collected from feedlots (n=29) were 0.5% and 25.9% by culture and PCR methods, respectively. Cattle harbor O104 serotypes other than H4, with O104:H7 being the predominant serotype and only a small proportion of them carried stx. DNA microarray and WGS analysis revealed absence of LEE-encoded virulence genes in bovine and human O104 strains. Escherichia coli O104:H7 has the potential to be a diarrheagenic foodborne pathogen in humans, since they possess stx1c and genes that code for enterohemolysin and a variety of adhesins. Data on prevalence, concentration and virulence potential of non-O157 E. coli serogroups, including O104, isolated from cattle feces are essential to design effective intervention strategies to reduce the potential to cause human foodborne illness outbreaks.
Keywords: E. coli; Cattle; Feces; Detection; Quantification